Susan Glaspell’s “Trifles” in the Light of Ecofeminism - Elmira Bazregarzadeh (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2019)
Throughout historical decades the unfair system of life in patriarchal societies and the oppression of women by men have always been key concepts in the literature of the world that have given rise to hot topics of discussion among different nations, questioning the real motive behind such trends. Hence, by examining Susan Glaspell’s “Trifles” through the lens of Ecofeminism the present paper aims to show how it can be considered as an ecofeminist work of literature doing away with the notions that pertain to the oppression of women and Nature by men.